«Продовольчі експедиції» та «авоська»: споживчі пристрасті «homo sovieticus» у сучасній прозі - Даниленко, Л. (Слово і Час, 2021)
У статті розглянуто питання споживчих інтересів радянської людини на прикладі творів О. Ільченка «Збирачі туманів» і С. Батурина
«Шизґара». Пояснено художні ідеї розвінчання міфів про добробут громадян СРСР, проаналізовано панораму повсякденного життя в умовах
продовольчого дефіциту, простежено суголосність авторських інтерпретацій як достовірність змалювання пережитого. Зазначено, що
відтворення сутності уніфікованої моделі «homo sovieticus» виявляє
нікчемність і небезпечність тоталітарної системи, нівелює можливість ностальгійних «зітхань» за радянським минулим. Contemporary Ukrainian prose has been actively appealing to the memory of the Soviet
past recently. Especially interesting is the literary reconstruction of everyday life that creates
a background for demonstrating a specific type of ‘homo sovieticus’.
A discussion on this large-scale and promising process has already started within literary
studies. The paper deals with O. Ilchenko’s “Fog Pickers” and S. Baturyn’s “Shyzgara”,
which represent the everyday life of Kyiv in the Soviet era. The focus is on the literary treatment of consumerism as a feature of a unified model representing the Soviet man.
The researcher explains the ideas of debunking the myths about happy life in the USSR,
analyzes the ways of creating the panoramic view of everyday life, traces the consistency of
the authors’ interpretations that shows how accurately the experiences are depicted. The
gastronomic routes of Kyiv residents, the methods of obtaining the foodstuffs, the social
relationships established during purchases presented in the literary works are worth special
attention. The writers are definitely critical regarding everyday living conditions in the recent
past. They put characteristic features of the Soviet everyday life at the center of events,
namely the lines in the stores of all kinds and their primitive range of products. Some Soviet
euphemisms related to the food theme have been explained in the paper as well.
The researcher comes to the conclusion that reconstruction of the everyday life of a
Soviet man in the works by O. Ilchenko and S. Baturyn reveals the despicable nature and
danger of the totalitarian system, shows the groundlessness of the nostalgic gasps for the
Soviet Union. The literary representation of life in the USSR prompts one to reflect on the
true values and uphold human dignity in a free state.